1985
DOI: 10.1021/bi00345a024
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Overhauser effect studies of the conformations and binding site environments of deoxynucleoside triphosphate substrates bound to DNA polymerase I and its large fragment

Abstract: The conformations and binding site environments of Mg2+TTP and Mg2+dATP bound to Escherichia coli DNA polymerase I and its large (Klenow) fragment have been investigated by proton NMR. The effect of the large fragment of Pol I on the NMR line widths of the protons of Mg2+TTP detected one binding site for this substrate with a dissociation constant of 300 +/- 100 microM and established simple competitive binding of deoxynucleoside triphosphates at this site in accord with previous equilibrium dialysis experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
43
0

Year Published

1986
1986
2007
2007

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 37 publications
7
43
0
Order By: Relevance
“…This work has been motivated because of reports of intermolecular transferred NOE contacts observed experimentally (e.g., Refs. [15][16][17][18][19][20][21][22][23], as well as the realization by us [11,14] and *To whom correspondence should be addressed. A copy of the CORCEMA program may be obtained from this author.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…This work has been motivated because of reports of intermolecular transferred NOE contacts observed experimentally (e.g., Refs. [15][16][17][18][19][20][21][22][23], as well as the realization by us [11,14] and *To whom correspondence should be addressed. A copy of the CORCEMA program may be obtained from this author.…”
Section: Introductionmentioning
confidence: 93%
“…When the exchange rate is very fast on the relaxation rate scale, the intensities become independent of the exchange rates, and the analysis of the intraand inter-TrNOESY is simpler [14]. The experimental observation of inter-TrNOESY contacts between a ligand and a large macromolecule by a number of investigators [15][16][17][18][19][20][21][22][23]32] establishes that a quantitative measurement of these intensities is indeed possible for small to moderate-sized complexes. Anglister and co-workers [21] have successfully identified interTrNOESY contacts between an antibody/antigen complex using difference-NOESY methods as well as a perdeuterated antibody.…”
mentioning
confidence: 96%
“…In the first reports on KF, it was suggested that the first conformational change may reflect reorientation of the triphosphate moiety of the incoming nucleotide to interact with side chains of the enzyme (28). This hypothesis was put forward to explain the observation made by Mildvan and colleagues that the orientation of the triphosphate and its interaction with divalent cation change in a KF ternary complex (38,39). Recently, it has been suggested that the conformational change defined kinetically may be related to changes in the orientation of the fingers subdomain observed crystallographically (12,40,41).…”
Section: Conformational Changes During 3d Pol -Catalyzed Nucleotide Imentioning
confidence: 99%
“…Further complicating matters is the absence of a clear structural explanation for the conformational change observed kinetically. Structural explanations range from inter-and intra-domain rearrangements (10 -12) to triphosphate reorientation (1,7,(13)(14)(15)(16)(17).…”
mentioning
confidence: 99%